More spiritual than religious: Concurrent and longitudinal relations with personality traits, mystical experiences, and other individual characteristics - Chen, Zhuo Job; Cowden, Richard G.; Streib, Heinz (Frontiers in Psychology, 2023)
People who self-identify as predominantly spiritual constitute a considerable and well-established part of the religious landscape in North America and Europe. Thus, further research is needed to document predictors, correlates, and outcomes associated with self-identifying primarily as a spiritual person. In the following set of studies, we contribute to some of these areas using data from German and United States adults. Study 1 (n = 3,491) used cross-sectional data to compare four religious/spiritual (R/S) self-identity groups—more religious than spiritual (MRTS), more spiritual than religious (MSTR), equally religious and spiritual (ERAS), and neither religious nor spiritual (NRNS)—on sociodemographic characteristics and a range of criterion variables (i.e., Big Five personality traits, psychological well-being, generativity, mystical experiences, religious schemata). In Study 2 (n = 751), we applied the analytic template for outcome-wide longitudinal designs to examine associations of the four R/S self-identifications with a range of subsequent outcomes (assessed approximately 3 years later) that were largely comparable to the criterion variables assessed in Study 1. The cross-sectional and longitudinal findings from these complementary studies provide further evidence of differences between these four categories of R/S self-identification, including strong evidence in both studies of an association between the MSTR self-identity and mysticism.